State Land Dispute Resolution Pinda Nabati-Yasa Kediri City (Study of Case Decision Number 61/Pdt.G/2016/PN.Kdr) - Nurbaedah (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2026)
This study examines the legal considerations in Case Decision Number 61/Pdt.G/2016/PN.Kdr jo Number 498/PDT/2017/PT SBY jo Number 2245 K/Pdt/2018 jo Number 780 PK/Pdt/2020 concerning a state land dispute in Kediri City (the Pinda Nabati-Yasa case) and the legal consequences of those considerations on the court rulings. This research employs a normative or doctrinal legal method carried out through library research. The statutory approach (Statute Approach) is applied and the research is descriptive in nature. Primary legal materials consist of applicable legislation, while secondary legal materials consist of the court decisions under study. Data are analyzed qualitatively in a descriptive manner. The findings show that the Kediri District Court declared the plaintiff’s claim inadmissible (niet ontvankelijke verklaard) on the grounds of formal defects in the statement of claim, insufficient defendants (plurium litis consortium), unclear boundaries of the disputed object, and unidentified occupants. The East Java High Court upheld this reasoning as legally correct. The Supreme Court found that the Judex Facti decision was not contrary to law. The Review Panel likewise held that no judicial error or manifest mistake existed in the Judex Juris decision. Consequently, the plaintiff’s claim was consistently declared inadmissible at all levels of adjudication.